Peran Lembaga Keuangan Mikro Islam dalam Meningkatkan Kesejahteraan Pengusaha Mikro - Tenny Badina; Rita Rosiana (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study is to analyze the structure and development as well as the problems and challenges faced by Islamic microfinance institutions in improving the socio-economic welfare of Islamic micro-entrepreneurs in the province of Banten. Islamic microfinance institutions have a social purpose in addition to the goal of obtaining profits that can be utilized by micro-entrepreneurs to develop their businesses. Islamic microfinance institutions have the potential to act as a mechanism for banking institutions. Data were analyzed based on micro-entrepreneurs with field survey methods and descriptive analysis. Field visits and interviews will be organized and conducted face-to-face with the manager of the microfinance institution. In the semi-structured interview process, respondents were asked to express their views on the research problem. It is hoped that the results of this study will obtain opinions from respondents regarding the role of Islamic microfinance intitutions in (1) improving the socio-economic welfare of micro entrepreneurs, (2) problems faced by microfinance institutions in distribute financing to micro-entrepreneurs. In general, respondents thinks that operations in Islamic microfinance institutions are currently not optimal due to several existing limitations. Respondents strongly agree that Islamic microfinance institutions should provide products, services, and instruments to respond to the needs of the poor in overcoming poverty and of course the services, products, and instruments offered must be distinguishable from other services, products, and instruments.